Analysis of The Effect Of Working Capital Rules On Levels Of Agricultural Companies Profitability In Indonesia Stock Exchange - Kristi Andari; Ahmad Azmy (Journal of Management and Leadership, 2019)
This study aims to analyze the effect of Working Capital Turnover, Inventory Turnover, and Accounts Receivable Turnover to the Profitability of the Company, either partially or simultaneously and to analyze how big the effect on agricultural companies listed on the Indonesia Stock Exchange (BEI). The object of this study were 16 agricultural companies listed on the Indonesia Stock Exchange. The data used are secondary data obtained and the publication of financial statements for five years, the period of 2012 to 2016. The method used in this study is the method of multiple regression analysis. From this research it can be seen that partially Receivable Turnover variable has a significant positive effect on Return On Assets and Inventory Turnover have a significant negative effect on Return On Assets. But the Working Capital Turnover variable has no significant effect. Simultaneously all independent variables have a significant effect on the dependent variable. The result of determination coefficient is 0.195320, meaning the ability of independent variable in explaining the dependent variable is 19,5%, while the rest 80,5% is explained by other variable not included in research equation model.